An Examination of the Impact of Using Marketplaces to Promote the Growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia - Dimas Aditya Prabowo; Chloe Tariazela; Andzelika Birgithri (Startupreneur Business Digital (SABDA Journal), 2024)
Marketplaces have become a critical component in the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The availability of a marketplace platform has a substantial impact on MSMEs' growth. The purpose of this study is to assess the impact of marketplaces on the growth of MSMEs by taking into account the elements that influence their integration into the digital ecosystem. The quantitative methodology was utilized to collect data from MSME traders who used the marketplace to market their items. The marketplace's presence has greatly enhanced sales and had a favorable impact on their business operations. Market access is open from Sabang to Merauke thanks to the information technology network. This data is evaluated statistically to determine the association between market presence and MSME business growth. The findings of this study can help MSMEs gain a better understanding of how to use marketplaces to boost exposure, sales, and overall growth. The practical ramifications of this research are supposed to assist MSME owners in developing marketing strategies for their products and services via marketplace platforms. This research will also contribute to scholarly literature on the development of MSMEs in the digital era.